(untitled) (Research, Society and Development, 2022)
Objective: To analyze the challenges and reflexes of communication between the multidisciplinary team in the context of management in Primary Health Care. Methodology: qualitative approach, integrative literature review type. Results and discussion: the total of 773 articles searched in repositories databases of articles in the health area, 46 studies were excluded due to duplicity and 12 studies were excluded because they did not allow free access through the link, six were chosen that answered the research question, after the thematic analysis, the following category was seized : challenges and reflexes of communication between a multidisciplinary team in the context of management in Primary Health Care (PHC). Conclusion: The main challenges identified were related to: communication difficulties; lack of instruments for the integration of federated entities; lack of effective mechanisms of interaction between in PHC “teams-management-users”, lack of knowledge on the part of managers regarding models and tools to improve communication that will reflect on the fluidity of information, facilitating dialogue between the actors that make up the PHC, also reflecting on the quality of management and service provided to users. Communication is shown to be closely related to the quality of services provided to the community, when legitimate and effective, communication contributes to the harmony and fluidity of information, facilitating dialogue between the actors that make up PHC, reflecting on the attention to users and quality. management, minimizing the challenges and enhancing the positive effects in the health area.